الهيدروكسي يوريا في علاج فقر الدم المنجلي (Latakia University Journal -Medical Sciences Series, 2019)
تهدف هذه الدراسة إلى إظهار فوائد الهيدروكسي يوريا المخبرية والسريرية في علاج فقر الدم المنجلي، وقد شملت هذه الدراسة (50) مريضاً مصاباً بفقر الدم المنجلي ممن تعرضوا لثلاث نوب ألمية أو أكثر في العام السابق للدراسة، أو خضعوا لنقل دم متكرر أو استشفاء متكرر ( ثلاث مرات سنوياً على الأقل ) أو تعرضوا لنشبة دماغية أو متلازمة صدر حادة أو تشظي طحال، أو يعانون من فقر دم شديد عرضي. تم البدء بالعلاج بجرعة ابتداءً من 15 مغ / كغ يومياً حتى30 مغ / كغ / يومياً، وقد تمت مراقبة هؤلاء المرضى كل 3 أشهر مخبرياً وسريرياً ( لمدة عام )، وأظهرت النتائج التحسن المخبري الملحوظ في قيم / HBF - MCV - HB / مع الانخفاض الواضح في قيمHBS وكذلك حدث تحسن سريري من خلال انخفاض معدل تكرر النوب الألمية، ومعدل نقل الدم ولكن كان عدد المرضى غير المستجيبين لهذا العلاج هو (5) مرضى إذ لم ترتفع نسبة الخضاب الجنيني لديهم إلى 15 % بعد عام كامل من العلاج. This study aims to assess the laboratory and clinical benefits of hydroxyurea in the treatment of sickle cell disease. This study includes (50 ) patients of SCD who had  reported at least three painful crises in the previous year, or had  reported at least three transfusions or hospitalization in a year, or who had a history of stroke, acute chest syndrome or splenic sequestration, or who had systemic sever anemia. Hydroxyurea was gradually increased from an initial dose of 15 mg / kg / d to 30 mg / kg / d. These patients were monitored by 3-month visits for one year to assess laboratory changes and clinical efficacy. Significant hematologic changes included increase in (HB - MCV- HBF) and decrease in HBS. And there was decrease in the number of transfusions, and painful crises. However, there were five patients who did not show any response to the treatment and the HBF concentration did not increase more than 15 % after a treatment for one year.